PENGEMBANGAN VIDEO ANIMASI POWTOON BERBASIS GENRE BASED APPROACH UNTUK PEMBELAJARAN MENULIS CERPEN - Uchi Arwidhakesuma, Hary Soedarto Harjono, Sophia Rahmawati (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2026)
This research aims to develop learning media in the form of animated videos based on Powtoon with a Genre Based Approach to improve the short story writing ability of class VIII students at SMP Negeri 17 Jambi City, as well as assessing their level of feasibility. Therefore, the use of Powtoon-based animated videos uses a Genre Based Approach with interesting media and modern learning methods, so that it can overcome the problem of students' ability to write short stories. The research method uses Research and Development (R&D) with a 4D model, which is limited to the define, design, develop and disseminate stages. However, this research is limited to development. Research subjects included material experts, media experts, Indonesian language teachers, and class VIII students at SMP Negeri 17 Jambi City. Data was collected through interviews, questionnaires and documentation, then analyzed quantitatively descriptively. The validation results show that this media is very suitable for use. Validation by material experts reached 92%, media experts 82.35%, teacher assessment 91.17%, and student trials in small groups 92% and large groups 96.25%. The research conclusion states that Powtoon-based animation videos using the Genre Based Approach are effective as a medium for learning to write short stories for class VIII students at SMP Negeri 17 Jambi City.